Cringing at Benevolence - McCrary, Charles (Method & theory in the study of religion, 2024)
Engaging with Logan’s third chapter, on the American Seamen’s Friends Society, this piece reflects on what it means to cringe in the context of a benevolent or charitable relationship. People cringe when they are made painfully aware of the gap between their self-conception (and/or their ideal self) and the way others perceive them. Logan shows us, in her study of the ASFS, the cringeworthy nature of antebellum benevolent societies: they learned about the objects of their benevolence (in this case, sailors), performed rituals alongside them, and attempted to befriend them, and yet they did not ultimately want to be them or be like them but, rather, to change them.